Identifying the differences in mechanisms of mycophenolic acid controlling fucose content of glycoproteins expressed in different CHO cell lines. Issue 11 (11th May 2016) - Zhang, An; Tsang, Valerie Liu; Markely, Lam R.; Kurt, Lutfiye; Huang, Yao‐Ming; Prajapati, Shashi; Kshirsagar, Rashmi
ABSTRACT: In the biopharmaceutical industry, glycosylation is a critical quality attribute that can modulate the efficacy of a therapeutic glycoprotein. Obtaining a consistent glycoform profile is desired because molecular function can be defined by its carbohydrate structures. Specifically, the fucose content of oligosaccharides in glycoproteins is one of the most important attributes that can significantly affect antibody‐dependent cellular cytotoxicity (ADCC) activity. It is therefore important to understand the fucosylation pathway and be able to control fucosylation at the desired level to match predecessor materials in late stage and biosimilar programs. Several strategies were explored in this study and mycophenolic acid (MPA) was able to finely modulate the fucose content with the least undesired side effects. However, the response was significantly different between CHO cell lines of different lineages. Further experiments were then performed for a deeper understanding of the mechanism of fucosylation in different CHO cell lines. Results indicated that changes in the intracellular nucleotide involved in fucosylation pathway after MPA treatment are the main cause of the differences in fucosylation level response in different CHO cell lines. Differences in MPA metabolism in the various CHO cell lines directly resulted in different levels of afucosylation measured in antibodies produced by the CHO cell lines. Biotechnol. Bioeng. 2016;113: 2367–2376. © 2016 Wiley Periodicals, Inc. Abstract : Understanding the fucosylation pathway and being able to control this process at the desired level are critical for bioproduction of highly efficient therapeutic glycoproteins. In this study, the authors explored several strategies and mycophenolic acid (MPA) was able to finely modulate the fucose content with the least undesired side effects. Significant differences in fucosylation levels of three tested recombinant CHO cell lines (CHO‐DG44, CHO‐DXB11, and CHO‐S) were attributed to changes in the intracellular nucleotide involved in fucosylation pathway after MPA treatment due to differences in their MPA metabolism.